Immune landscape of inflammatory breast cancer suggests vulnerability to immune checkpoint inhibitors. (1st January 2021) - Bertucci, François; Boudin, Laurys; Finetti, Pascal; Van Berckelaer, Christophe; Van Dam, Peter; Dirix, Luc; Viens, Patrice; Gonçalves, Anthony; Ueno, Naoto T.; Van Laere, Steven; Birnbaum, Daniel; Mamessier, Emilie
ABSTRACT: Background . Anti-PD1/PDL1 immune checkpoint inhibitors (ICIs) showed promising results in breast cancer, and exploration of additional actionable immune checkpoints is ongoing. Inflammatory breast cancer (IBC) is an aggressive form of disease, the immune tumor microenvironment (TME) of which is poorly known. We aimed at providing the first comprehensive immune portrait of IBCs. Methods . From the gene expression profiles of 137 IBC and 252 non-IBC clinical samples, we measured the fractions of 22 immune cell types, expression of signatures associated with tertiary lymphoid structures (TLS) and with the response to ICIs (T cell-inflamed signature: TIS) and of 18 genes coding for major actionable immune checkpoints. The IBC/non-IBC comparison was adjusted upon the clinicopathological variables. Results . The immune profiles of IBCs were heterogeneous. CIBERSORT analysis showed profiles rich in macrophages, CD8+ and CD4 + T-cells, with remarkable similarity with melanoma TME. The comparison with non-IBCs showed significant enrichment in M1 macrophages, γδ T-cells, and memory B-cells. IBCs showed higher expression of TLS and TIS signatures. The TIS signature displayed values in IBCs close to those observed in other cancers sensitive to ICIs. Two-thirds of actionable immune genes ( HAVCR2/TIM3, CD27, CD70, CTLA4, ICOS, IDO1, LAG3, PDCD1, TNFRSF9, PVRIG, CD274/PDL1, and TIGIT ) were overexpressed in IBCs as compared to normal breast and two-thirds were overexpressed in IBCs versus non-IBCs, with very frequent co-overexpression. For most of them, the overexpression was associated with better pathological response to chemotherapy. Conclusion . Our results suggest the potential higher vulnerability of IBC to ICIs. Clinical trials.